Syafiq & Zahidah the best for English Camp 2010 - Sarah, Zulkiple; Nor Suhardiliana, Sahar (Pusat Bahasa Moden dan Sains Kemanusiaan, 2010)
9 - 11 May 2010. Muhammad Syafiq Sabtu and Zahidah Ansari were crowned as the best male and female participant during UMP’s 2010 English Camp, held at Taman Pertanian Sultan Haji Ahmad Shah Indera Mahkota, Kuantan. The decision was made based on both being outstanding and enthusiastic participants during the three days and two nights camp. 30 first year UMP students and volunteers from various faculties were selected based on their performance in MUET and UHL2312 Technical English course.